2023
DOI: 10.1002/smll.202306273
|View full text |Cite
|
Sign up to set email alerts
|

Ferric Oxide Nanocrystals‐Embedded Co/Fe‐MOF with Self‐Tuned d‐Band Centers for Boosting Urea‐Assisted Overall Water Splitting

Jiameng Liu,
Linghao He,
Zheng Tao
et al.

Abstract: A novel semiconductive Co/Fe‐MOF embedded with Fe2O3 nanocrystals (Fe2O3@CoFe‐MOF) is developed as a trifunctional electrocatalyst for the urea oxidation reaction (UOR), oxygen evolution reaction (OER), and hydrogen evolution reaction for enhancing the efficiency of the hydrogen production via the urea‐assisted overall water splitting. Fe2O3@CoFe‐TPyP‐MOF comprises unsaturated metal‐nitrogen coordination sites, affording enriched defects, self‐tuned d‐band centers, and efficient π–π interaction between differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…Based on the above results, the excellent OER performance of Ni NDC-Co/CP can be attributed to several factors: (1) The presence of rough nanosheets facilitated by Co 3 O 4 , which are modified to enhance the contact area with the electrolyte, thereby expediting electron transfer under an electric field . (2) The introduction of Co 2+ leads to the generation of Co–O–Ni–O–Co units in Ni NDC-Co, optimizing the d-orbitals of Ni 2+ and promoting the formation of Ni 3+ , thereby reducing the reaction energy barrier in the OER process. , (3) In situ growth avoids the use of binders and preserves the catalytic capacity of the catalyst as much as possible …”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Based on the above results, the excellent OER performance of Ni NDC-Co/CP can be attributed to several factors: (1) The presence of rough nanosheets facilitated by Co 3 O 4 , which are modified to enhance the contact area with the electrolyte, thereby expediting electron transfer under an electric field . (2) The introduction of Co 2+ leads to the generation of Co–O–Ni–O–Co units in Ni NDC-Co, optimizing the d-orbitals of Ni 2+ and promoting the formation of Ni 3+ , thereby reducing the reaction energy barrier in the OER process. , (3) In situ growth avoids the use of binders and preserves the catalytic capacity of the catalyst as much as possible …”
Section: Resultsmentioning
confidence: 95%
“…64 (2) The introduction of Co 2+ leads to the generation of Co− O−Ni−O−Co units in Ni NDC-Co, optimizing the d-orbitals of Ni 2+ and promoting the formation of Ni 3+ , thereby reducing the reaction energy barrier in the OER process. 45,65 (3) In situ growth avoids the use of binders and preserves the catalytic capacity of the catalyst as much as possible. 66…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Therefore, UOR-assisted water splitting can significantly reduce the potential at the anode, which is very beneficial for reducing electrolytic energy consumption. 51 EIS was employed to analyze the reaction kinetics of CoNi-LDH/Fe MOF/NF at different potentials for OER and UOR, as can be seen in Figure 4c,e. The Nyquist plots demonstrate a gradual reduction in the radius of the semi arc as the applied potential increases, indicating a gradual decrease in the R ct of the catalytic reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The overpotentials of UOR are significantly lower than those of the OER. Therefore, UOR-assisted water splitting can significantly reduce the potential at the anode, which is very beneficial for reducing electrolytic energy consumption …”
Section: Resultsmentioning
confidence: 99%
“…For instance, Liu et al integrated CoFe-TPyP-MOF with Fe 2 O 3 to tune the d-band of the catalyst for improved UOR activity. 103 The resulting Fe 2 O 3 @CoFe-TPyP-MOF heterostructure featured unsaturated metal–nitrogen coordination sites, which led to enriched defects, self-tuned d-band centers, and efficient π–π interactions between different layers. 103 XPS and XAS studies confirmed the modulation of coordination and electronic properties of the catalyst due to the formation of the heterostructure.…”
Section: Anodic Oxidation Reactions With Mofsmentioning
confidence: 99%